2021
DOI: 10.1021/acsami.1c01621
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Noble-Metal-Free Catalyst for the Selective Aerobic Oxidation-Knoevenagel One-Pot Reaction: Encapsulation of Polyoxometalates into an Alkylamine-Modified MIL-101 Framework

Abstract: One-pot reactions offer economic and environmental advantages. Therefore, the design and synthesis of multifunctional catalysts capable of catalyzing multistep organic transformations are highly important. Herein, an effective bifunctional heterogeneous catalyst is presented. For the first time, the encapsulation of H5PMo10V2O40 (PMoV2) polyoxometalate into the cages of an alkylamine-modified MIL-101 using an optimized double-solvent method is reported. The obtained PMoV2@DETA-MIL-101 material displays a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…However, PMoV 2 @DETA-MIL-101 enabled this tandem reaction without the need of noble metal catalysts or base additives. [73] Li et al prepared MOF-808 and encapsulated Keggin-type H 3 PW 12 O 40 into that to generate HPW@MOF-808 catalyst for tandem transformation of levulinic acid to γ-valerolactone. To prepare the catalyst, MOF-808 was solvothermally synthesized in DMF using ZrOCl 2 .8H 2 O, 1,3,5-benzene tricarboxylic acid and formic acid.…”
Section: Multifunctional Pom-based Catalysts For Tandem Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PMoV 2 @DETA-MIL-101 enabled this tandem reaction without the need of noble metal catalysts or base additives. [73] Li et al prepared MOF-808 and encapsulated Keggin-type H 3 PW 12 O 40 into that to generate HPW@MOF-808 catalyst for tandem transformation of levulinic acid to γ-valerolactone. To prepare the catalyst, MOF-808 was solvothermally synthesized in DMF using ZrOCl 2 .8H 2 O, 1,3,5-benzene tricarboxylic acid and formic acid.…”
Section: Multifunctional Pom-based Catalysts For Tandem Reactionsmentioning
confidence: 99%
“…The results showed that benzyl alcohol was selectively converted to benzylidene malononitrile after 36 h. An aerobic oxidation of alcohols to aldehydes followed by the Knoevenagel condensation has been reported using either noble metal catalysts or noble‐free metal catalysts in the presence of a base additive. However, PMoV 2 @DETA‐MIL‐101 enabled this tandem reaction without the need of noble metal catalysts or base additives [73] …”
Section: Catalytic Activity Of Pom‐based Hybridsmentioning
confidence: 99%
“…† As shown in entries 2-4 of Table 4, the high yields were achieved from benzaldehydes with electron-withdrawing groups (-NO 2 , -F and -Br), which could effectively reduce the electron density around the CvO group. [70][71][72][73] In contrast, benzaldehyde derivatives with electron-donating groups (-CH 3 ) had a certain blocking effect on the conversion process, which slightly reduces the yield (entries 5 and 6, Table 4). In addition, entries 6 and 7 exhibit that the significantly decreased yields of 2-((3,4-dimethoxyphenyl)methylene)propanedinitrile and 2-((3,4,5-trimethoxyphenyl)methylene)propanedinitrile should be attributed to the large molecular size of the substrates, which greatly affected the large-scale diffusion of molecules in channels and the efficient contact with active sites.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…Tandem reactions usually require multifunctional catalysts that are able to promote more than one single reaction [ 30 ]. The formation of a carbon–carbon bond through the selective aerobic oxidation of alcohols and consecutive Knoevenagel condensation reaction is one of the most fundamental transformations in organic chemistry [ 31 , 32 , 33 , 34 ]. In this context, various heterogeneous catalysts have been reported but possess numerous shortcomings, including poor stability, precious metals, and/or metal contamination, thereby hampering their practical applications [ 7 , 8 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%